Stopover ecology of five species of migratory songbirds at a coastal site in the Pacific flyway - Barton, Regina A. (Kansas State University, 2012)
The migratory period is a critical time for birds. Population declines in long-distance migratory birds have been associated with trophic mismatches among climate change, timing of food availability, and timing of migratory movements. Studies on migratory songbirds have been limited to eastern North America and Europe, and migration strategies of birds may differ along the Pacific flyway. We evaluated the stopover ecology of five species of migratory songbirds at a coastal site in northern California. We found variation in changes in timing of spring migration, but consistent changes in timing of autumn migration over a 22-year period. Timing of spring migration advanced for Swainson’s Thrushes (Catharus ustulatus) and Yellow Warblers (Setophaga petechia), was compressed for Pacific-slope Flycatchers (Empidonax difficilis) and Wilson’s Warblers (Cardellina pusilla), but was protracted for Orange-crowned Warblers (Oreothlypis celata). In contrast, timing of autumn migration was delayed for Pacific-slope Flycatchers, Orange-crowned Warblers, and Yellow Warblers, but was protracted for Wilson’s Warblers. Warm, wet conditions were associated with advanced spring migration, and warm, dry conditions were associated with delayed autumn migration. Changes in timing of migration related to climate conditions were strongest for Pacific-slope Flycatchers and Orange-crowned Warblers. Stopover duration of our five study species was longer than songbirds in eastern flyways, and on average, was longer in spring than autumn. Pacific-slope Flycatchers and Yellow Warblers had longer stopovers in spring, whereas Swainson’s Thrushes and Wilson’s Warblers stopped had longer stopovers in autumn. Birds captured at low body mass had longer stopovers in spring and autumn. Migratory birds in western North America may have different migration strategies because of differences in climate and geography, but more study is needed to discover migratory routes and compare our results to other stopover sites along the Pacific flyway. Understanding differences in migration strategies of different populations of the same species are important in directing conservation efforts, especially in light of ongoing climate change.
Keywords: Climate indices; Mark-recapture; Migration timing; Stopover ecology; Biology (0306); Ecology (0329)